IMPLEMENTASI STRATEGI READING ALOUD UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA FASE B SEKOLAH DASAR - Henik Monicha Putri; Desi Setiyadi (JISPE Journal of Islamic Primary Education, 2026)
The main problem frequently encountered at the elementary school level, especially among Phase B students, is the low ability to read fluently and comprehend text content in its entirety. This condition hinders the overall success of the students' learning process because mastery of reading literacy is the fundamental basis for students to effectively absorb material, as well as understand and process various subjects. This study aims to implement the reading aloud strategy as a concrete effort to improve technical reading skills, in addition to fostering a high interest in reading and building students' self-confidence and courage to perform. The Classroom Action Research method was conducted in two cycles, with each cycle comprising the stages of planning, implementation, observation, and reflection on learning outcomes. The research subjects consisted of 27 third-grade students at SD Yos Sudarso Payung Batu. Data were collected through reading skill tests, activity observation sheets, in-depth interviews, and activity documentation. The results indicated a highly significant improvement in ability, where the students' average score increased from 66 to 83, with classical learning completeness reaching 89%. The novelty of this research lies in the integration of improving reading techniques, understanding meaning, and strengthening character in one learning framework which has not been fully discussed in similar research. This strategy proved effective in enhancing reading fluency, pronunciation clarity, accuracy of intonation and pauses, as well as comprehension of the text's meaning. The implementation of this strategy serves as a targeted and meaningful learning solution, capable of creating a harmonious, safe, and enjoyable learning environment for students.